Application of finite element analysis to evaluate optimal parameters for bone/tooth drilling to avoid thermal necrosis. Issue 1 (1st January 2021) - Prabhu, Nayana; Shetty, Dasharathraj K; Naik, Nithesh; Shetty, Nagaraja; Kalpesh Parmar, Yash; Patil, Vathsala; Sooriyaperakasam, Nilakshman
Abstract: The paper seeks to address issues that arise during the drilling and fixation of bones in orthopedic, orthodontic and implant surgeries. Thermal necrosis is one of the widespread problems that occurs during bone/tooth drilling and which can lead to implant failures. The highest registered temperature during drilling is 86°C. However, when the temperature is increased beyond 47° C during the drilling process, it can often lead to osteonecrosis. The possibility of thermal necrosis can be minimized by controlling the drilling parameters. However, optimal parameter values identified by various researchers have not been complied so far, primarily because of the effects of multifactorial constraints. Overall, the drilling bore speed and the feed rate are found to be the most influential parameters in triggering thermal injuries in the course of time. The drilling speed is also more important to the feed rate. In addition, osteological location also increases the probability of necrosis by multiple means in terms of anatomy. A thermocouple is used to evaluate in vivo temperature conditions during the drilling process. However, given the uncertainty and the practical errors that occur during the experimental measurements, the finite-element analysis (FEA) is proposed in most studies. This paper explores the existing state of literature and summarizes various drilling methods and assess the related parameters using FEA. It also describes the impact of various constraints in detail to explore the optimum drilling parameters in order to minimize the danger of thermal necrosis.